The Philosophy of Pesantren Education: A Study on the Foundations of Innovation in Pesantren Development - Sumadi, Eko; Nugroho, Puspo; Syah, Muhammad Noor Sulaiman (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to examine the philosophy of pesantren education as the philosophical foundation for innovation in the development of Islamic boarding schools amid the dynamics of social change and the demands of modernity. The study is grounded in the assumption that pesantren innovation is not merely technical or pragmatic in nature, but is deeply rooted in the ontological, epistemological, and axiological constructions of pesantren education. Employing a qualitative approach with a multi-site case study design, the research was conducted at Mahirul Hikam Assalafi Islamic Boarding School in Semarang Regency and Nurul Qur’an Islamic Boarding School in Boyolali. Data were collected through observation, in-depth interviews, and document analysis, and subsequently analyzed using an interactive analysis model. The findings reveal that ontologically, pesantren education is based on a conception of human beings as religious and social entities; epistemologically, it relies on the selective integration of revelation, classical Islamic scholarly traditions, and modern rationality; and axiologically, it is oriented toward moral formation, communal well-being, and social responsibility. These philosophical foundations serve as the primary basis for pesantren innovation, encompassing institutional development, curriculum design, and educational programs. The innovations implemented by both pesantren are contextual and gradual in nature, aimed at preserving the tradition of tafaqquh fi al-dīn while enhancing the relevance of pesantren education to contemporary societal needs. This study underscores that the philosophy of pesantren education plays a strategic role in bridging tradition and modernity, and functions as a normative framework for adaptive and sustainable pesantren development.